Keefektifan Model Pembelajaran Sort Card pada Pembelajaran IPS terhadap Hasil Belajar Siswa Kelas III SD Negeri Karangroto 04 Kota Semarang - Dewi, Wiwik Kumala (International Journal of Elementary Education, 2018)
The problem revealed in this study is how effective the Sort Card learning model is on social studies learning towards the learning outcomes of third grade students of Karangroto 04 State Elementary School in Semarang City. The purpose of this study was to determine the effectiveness of the Sort Card learning model on social studies learning on the learning outcomes of third grade students of Karangroto 04 Public Elementary School in Semarang City. This type of research is quantitative. The population in this study were class III students totaling 30 students and the design used for this study using One-Group Pretest-posttest Design. Data collection methods used are observation, tests, interviews, and documentation. The results of the study revealed the average value of pretest students 43,74 and the average posttest score of students was 88.86. From the calculation using the t-test, it is obtained t_count = 16.034 and ttable = 2.045 with db = 30-1 at the significant level α = 5%, so that t_count > t table is 16,034 > 2,045. So Ho is rejected and Ha is accepted. It can be concluded that the sort card model is effective against student learning outcomes. Based on the results of this study the suggestions that can be conveyed are expected teachers can use the sort card learning model in teaching and learning activities, especially social studies subjects